The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1002/cphc.200700477
|View full text |Cite
|
Sign up to set email alerts
|

Conformation and Interaction of a d,l‐Alternating Peptide with a Bilayer Membrane: X‐ray Reflectivity, CD, and FTIR Spectroscopy

Abstract: Peptides with alternating amino acid configuration provide helical secondary structures that are especially known from the membrane channel and pore-forming gramicidin A. In analogy to this natural D,L-alternating pentadecapeptide, the potential of D,L-alternating peptides for membrane insertion is investigated using the model dodecamer peptide H-(Phe-Tyr)(5)-Trp-Trp-OH. This aromatic peptide is introduced as a novel pore-forming synthetic analogue of gramicidin A. It forms a well-organized homodimer similar t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(36 citation statements)
references
References 54 publications
2
34
0
Order By: Relevance
“…Considering the peptide structure as discussed earlier for oligomer 7 on the basis of CD and FTIR studies and comparing them to the extensively studied d,l-alternating configurated gramicidin A, two predominant structures are conceivable for these peptides. [16] Although the occurrence of the b -helix with a 3.3 pitch would feature a length of approximately 21 . [46][47][48][49][50] Considering these facts in addition to the CD results and previous studies, the distance indicated in the electron density difference curves by the major peaks that are located right beneath the lipid head-groups additionally suggest the existence of a membrane-spanning b 5.6 -helix.…”
Section: -Helices and X-ray Reflectivitymentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the peptide structure as discussed earlier for oligomer 7 on the basis of CD and FTIR studies and comparing them to the extensively studied d,l-alternating configurated gramicidin A, two predominant structures are conceivable for these peptides. [16] Although the occurrence of the b -helix with a 3.3 pitch would feature a length of approximately 21 . [46][47][48][49][50] Considering these facts in addition to the CD results and previous studies, the distance indicated in the electron density difference curves by the major peaks that are located right beneath the lipid head-groups additionally suggest the existence of a membrane-spanning b 5.6 -helix.…”
Section: -Helices and X-ray Reflectivitymentioning
confidence: 99%
“…[16] The motif derived from gramicidin A is characterized by a membrane-spanning b 5.6 -helical dimer of antiparallel oriented and d,l-alternating configurated peptides. The tubular structures are supposed to anchor at the polar-hydrophobic head-group interface with their C-terminal tryptophane moieties spanning the hydrophobic membrane core without complete penetration of the lipid head-group region ( Figure 4).…”
Section: Transmembrane Peptide Design and Solid-phase Peptide Synthesismentioning
confidence: 99%
“…[2] Yet, due to its hydrophobicity, small size (15 residues), and ready availability, including the ease with which it can be synthesized or modified, gramicidin A (gA) has proven most valuable as a model for understanding the structure and function of transmembrane ion channels. [2] Accordingly, a number of gA derivatives [2] and model b-helical peptides [7][8][9][10][11][12][13][14][15][16] have been prepared over the past three decades; because the motive of these studies was to understand and mimic the structure and function of gA, these peptides were all hydrophobic and were examined almost exclusively in nonpolar media. [17] Meanwhile, the b-helical conformations of gA have been shown to be unstable in polar solvents; [18] for example, although gA is b-helical in methanol or ethanol that contains high concentrations of the nonpolar solvents chloroform or benzene, [18,19] the peptide is unstructured in the polar solvent dimethyl sulfoxide (DMSO).…”
Section: Introductionmentioning
confidence: 99%
“…FTIR spectra of the same peptide in water revealed that the β-sheet structure dominated at higher concentrations (76). The interaction of the polymer chain with conjugated peptide can be studied by X-ray reflectivity as well as CD and FTIR (77,78). Site-specific iodine labeling can be used to determine topology of the peptide within the self-assembled NPs by pinpointing the position of iodine label within NPs (77).…”
Section: Characterization Of Peptidomimetic Npsmentioning
confidence: 99%